2012
DOI: 10.1152/ajprenal.00646.2011
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral membrane K+channels in renal epithelial cells

Abstract: The major function of epithelial tissues is to maintain proper ion, solute, and water homeostasis. The tubule of the renal nephron has an amazingly simple structure, lined by epithelial cells, yet the segments (i.e., proximal tubule vs. collecting duct) of the nephron have unique transport functions. The functional differences are because epithelial cells are polarized and thus possess different patterns (distributions) of membrane transport proteins in the apical and basolateral membranes of the cell. K(+) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 140 publications
(192 reference statements)
1
39
0
Order By: Relevance
“…Basolateral K 1 efflux pathways play an important role in this process (21). By transporting K 1 extracellularly, basolateral potassium channels create a "leak" that recycles K 1 and helps to maintain the activity of the sodium pump (Figure 2).…”
Section: Basolateral K 1 Channelsmentioning
confidence: 99%
“…Basolateral K 1 efflux pathways play an important role in this process (21). By transporting K 1 extracellularly, basolateral potassium channels create a "leak" that recycles K 1 and helps to maintain the activity of the sodium pump (Figure 2).…”
Section: Basolateral K 1 Channelsmentioning
confidence: 99%
“…In the mouse kidney, KCNQ1 mRNA is expressed in the PT, DCT, CNT, CD, and glomeruli (Wang, 2004;Zheng et al, 2006). It is also distributed intensely and basolaterally in the DCT and CNT cells (Wang, 2004;Zheng et al, 2006), serving as part of the basolateral potassium channels (Hamilton and Devor, 2012). Recent research results have confirmed that KCNQ1-related potassium channels, which are highly expressed at the apical membrane of proximal convoluted tubule, underlie the K + reabsorption (Wang, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Basolateral outflow of the K + current by the potassium channel couples with the Na + -K + -ATPase pump current in order to balance the charge movement across the cell membrane. Thus, the basolateral potassium channel is suggested to maintain the intracellular electroneutrality by K + recycling and plays an essential role in the reabsorption of Na + (Dawson and Richards, 1990;Hamilton and Devor, 2012). Additionally, K + recycling across the membrane of kidney epithelial cells is necessary for the continuous function of the Na (Welling, 1997), suggesting that the basolateral potassium channel plays an important part in Cl -reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…Our current knowledge of body fluid Cl 2 homeostasis is mostly derived from studies of mammals. In the distal convoluted tubule (DCT) cell model of Cl 2 reabsorption in mammalian kidneys, Cl 2 enters the cell through an apical membrane via the sodium chloride co-transporter (NCC) and is ultimately extruded to the blood through a CLC-K chloride channel [3][4][5]. Previous studies in zebrafish identified NCC2b-expressing cells in the gills and skin as the major ionocytes responsible for Cl 2 uptake and thus these cells act in a similar manner to DCT cells in the mammalian kidney [6].…”
Section: Introductionmentioning
confidence: 99%
“…Other than the NCC2b-mediated CLC-2c Cl 2 uptake, pathways through SLC26 anion transporters might also participate in Cl 2 uptake in zebrafish [7] although the detailed mechanisms are still missing a lot of information and further investigation is needed. The ion transport mechanism for body fluid Cl 2 homeostasis appears to be conserved from fish to mammals [3][4][5]8]. Different hormones participate in the control and regulation of NCC function in mammalian kidneys.…”
Section: Introductionmentioning
confidence: 99%